Randomized clinical trial of heated high viscosity glass ionomer class ii restorations in deciduous molars: 12 months follow up - EREN GİRAY, FİGEN; KARGÜL, BETÜL; YILMAZ, MÜESSER AHU (My University, 2022)
Objective: New generation High Viscosity Glass Ionomer Cements (HVGICs) have enhanced physical and mechanical properties. By effectively closing the restoration margin, it ensures that the restorations will last longer. The aim of this study was to investigate the clinical performances of heat-cured versus non heated HVGIC in class II restorations of deciduous molars.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Dental caries; Glass ionomer cement; Deciduous tooth; MECHANICAL-PROPERTIES; IN-VITRO; SEALANTS; ART; PERFORMANCE; CEMENTS